Exploring the divergence in research focus and trends between domestic and International traditional handicraft studies - Liu, Haoran; Alli, Hassan; Md Yusoff, Irwan Syah (Cogent OA, 2024)
This study aims to compare and contrast the development and trends in traditional handicraft research within domestic and international contexts, offering insights for the future direction of traditional handicrafts in China. By utilizing data from the CNKI and Scopus databases, this research uses various functions in Citespace, including category analysis, institutional analysis, keyword co-occurrence analysis, and brust keyword detection. These analyses provide a comprehensive comparison of spatio-temporal relationships, publishing institutions, research fields, publication journals, research hotspots, and development trends. Notably, China’s research exhibits significant enthusiasm in areas such as digital preservation, rural revitalization, and targeted poverty alleviation, while foreign research demonstrates a higher emphasis on commercialization, sustainable products, and user perception. Additionally, China emphasizes cultural preservation and inheritance, whereas foreign research places a greater focus on economic value. In terms of research methods, China’s emphasis is on strategic social-level research, while foreign research leans towards technical product and platform research. Combining the insights from both domestic and foreign research highlights two primary characteristics of traditional handicraft application areas: proactive preservation and revitalization efforts in China compared to the commercialization and market orientation emphasis abroad, and a greater focus on cultural preservation in China versus economic value abroad, indicating distinct research content and approaches between the two contexts.